Angle Closure Glaucoma with Myopia - Chhipa, Shaukat Ali (Pakistan Journal of Ophthalmology, 2009)
Reporting a case of 30 years old man who presented with pain and blurring in his right eye in an offsite ophthalmic consulting clinic of The Aga Khan university hospital. On the basis of history and clinical examination he was diagnosed as a case of primary angle closure glaucoma (PACG), although his refractive status was myopic. Narrowing of anterior chamber angle and PACG are almost always associated with hyeropia. To my knowledge this rare combination of PACG and myopia has never been reported before in Pakistan. The patient was managed as for a PACG.